HOW MANAGERIAL ENVIROMENTAL CONCERN ENABLES THE SUSTAINABILITY GOVERNANCE IN HIGHER EDUCATION? - Alwindrajudi, Agus; Rahayu, Agus; Senin, Syamsul Hadi; Furqon, Chairul; Munawar, Asep (RADJA PUBLIKA, 2026)
This study examines how managerial environmental concern (MEC) enables sustainability governance in a private Indonesian university by tracing how environmental commitments become institutionalized. Using a 91-day qualitative case study, it triangulates semi-structured interviews with nine purposively selected participants, observations, and institutional documents, analyzed through thematic analysis supported by NVivo. Findings position MEC as a governance enabler that links leadership commitment to durable organizational arrangements through four connected mechanisms. First, MEC is embedded in strategic planning and performance management by integrating environmental indicators into institutional work plans and annual budgets. Second, it is structurally anchored through a dedicated coordinating team that mainstreams sustainability across planning, implementation, and evaluation, and formalizes operational guidance for energy efficiency, waste management, carbon footprint reporting, and green procurement. Third, MEC mobilizes scarce resources via incentive and control mechanisms, prioritizing funding for units showing strong green performance and requiring environmental criteria in infrastructure proposals. Fourth, MEC gains legitimacy through participatory forums involving academic and administrative staff and students in sustainability decisions. Together, these mechanisms stabilize sustainability initiatives beyond project-based efforts and offer a transferable pathway for private universities in developing contexts.